POPSI Its Fundamentals and Procedure based on a General Theory of Subject Indexing Languages - Bhattacharyya, G. (Journal of Information and Knowledge, 1979)
Aims at examining the fundamentals and procedure of POPSI (Postulate-based Permuted Subject Indexing) on the basis of an experiment. For this purpose, (1) enumerates the empirical facts of experience generalised from the experiment; (2) explains the fundamentals-Idea; Information, Informative formulation, Indicative formulation, Subject, Groups of subjects, Classification of subjects; Organizing classification and Associative classification Structures of subjects; Semantic structure; Elementary structure; and Syntactic structure-forming part of the intellectual foundation of POPSI. Formulates the set of general postulates pertaining to the elementary and syntactic structures of compound subject. Marks out the essential attributes of subject indexing languages; Define’s POPSI in terms of the steps involved in the procedure. Concludes as follows The idea of a purpose-oriented, postulate-based organisation Classification serving as the source of derivation by permutation of all possible associative classifications to supplement it in a definite context, is the characteristic feature of POPSI. Naturally it has a highly generalised, hospitable, versatile, and therefore adaptable intellectual foundation capable of guiding the formulation of consistent specific procedures of subject indexing for retrieval of (1) information qua information, (2) information ab-Ont the location of a body of information in the text of a document, and (3) information about the surrogates of documents. POPSI is amenable to computerisation. The potentiality of POPSI, as discovered till today, suggests that it can be regarded as an all-purpose indexing procedure so far as "information retrieval" is concerned.